Policy Of Merdeka Belajar Kampus Merdeka (Prophetic Education Perspective) - Saifullah, Ach.; Qomar, Mujamil; Aziz, Abd. (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Merdeka Belajar Kampus Merdeka policy supports student-centered learning and emphasizes student freedom and responsibility in learning. The purpose of this study is to explain the theoretical basis of Merdeka Belajar Kampus Merdeka, which places students at the center of learning, the role of prophetic education in shaping educational awareness in students, and Merdeka Belajar Kampus Merdeka from the perspective of prophetic education. The research uses qualitative analysis with a literature study approach. Sources of research data are taken from journals, papers, and other literature on the Merdeka Belajar Kampus Merdeka policy, which is student-centered learning; prophetic education in shaping educational awareness in students; and the Merdeka Learning Campus Merdeka policy seen from the perspective of prophetic education. The study results show that through the student-centered learning approach, students have a more authentic learning experience. This experience must be supported by the internalization of monotheistic values to form a solid educational awareness. Prophetic education can guide students in integrating humanization, liberation, and transcendence into independent learning. Personal experience, educational awareness, and prophetic education create an effective synergy to create a quality academic climate.